Telling histories : black women historians in the ivory tower - White, Deborah G. (Deborah Gray), 1949- (Gender & American culture., 2008)
The field of black women's history gained recognition as a legitimate field of study late in the twentieth century. Collecting stories that are both deeply personal and powerfully political, Telling Histories compiles seventeen personal narratives by leading black women historians at various stages in their careers. Their essays illuminate how--first as graduate students and then as professional historians--they entered and navigated the realm of higher education, a world concerned with and dominated by whites and men. In distinct voices and from different vantage points, the personal historie.